Investigating the Antibacterial, Antioxidant, and Cholesterol-lowering Properties of Yogurt Fortified with Postbiotic of Lactobacillus acidophilus and Lactiplantibacillus plantarum in the Wistar Rat Model - Sareh Davarzani; Mohammad Reza Sanjabi; Naheed Mojgani; Saeed Mirdamadi; Mostafa Soltani (Journal of Food Protection)
Postbiotics have gained attention in the food industry due to their functional properties and ease of use compared to their live parent cells. Postbiotics are the metabolic byproducts of probiotic microorganisms, offering advantages such as antimicrobial and anti-diabetic effects. The study aimed to explore the potential antibacterial, antioxidant, and cholesterol-lowering effects of postbiotics from Lactobacillus acidophilus (LA) and Lactiplantibacillus plantarum (LbP) through in vitro and in vivo studies. Freeze-dried postbiotics from L. acidophilus BLAC 258 and L. plantarum were used in yogurt to inhibit foodborne pathogens over a 21-day storage period at 4 °C. The cholesterol-lowering effects of the postbiotic yogurt were assessed in Wistar rats fed with Normal Basal Diet (NBD) and High Cholesterol Diet (HCD). All experiments were performed in triplicate, and the collected data were analyzed with a one-way ANOVA using SPSS v.20 (2021) software. The Tukey Honestly Significant Difference (HSD) test was used for means differences at the 95% confidence interval. The results showed that postbiotic-fortified yogurt exhibited significant antioxidant and antibacterial effects. The antioxidant capacity of the yogurt increasingly peaked at 48.81% on day 14. Also, Listeria monocytogenes counts in the postbiotic yogurt decreased by approximately 2 Log10 on day 3. High-cholesterol-fed rats receiving postbiotic yogurt experienced significant reductions in total cholesterol, triglycerides, and LDL levels. Overall results indicate that postbiotics functional yogurt might be a safe and effective strategy for managing cholesterol levels and inhibiting foodborne pathogens.